ANALYZING THE RELATIONSHIP BETWEEN TRAINING AND LOCAL GOVERNMENT PERFORMANCE OF KIKUUBE DISTRICT: A DESCRIPTIVE, CORRELATIONAL, AND A CROSS-SECTIONAL SURVEY. - Nelson Mwanje; Edmand Bakashaba (Student's Journal of Health Research, 2023)
Background: The study aimed to analyze the relationship between training and local government performance in the Kikuube district. Methodology: A descriptive, correlational, and cross-sectional survey was employed among Kikuube District staff employees, service commissioners, and political leaders at the district headquarters. Simple random sampling techniques and purposive samplings were used to select respondents to participate in this study. Simple random to give every employee an opportunity and a purposive sampling technique on selecting the only service commission staff in the district and the Chairperson Local council five- Kikuube district with in-depth information regarding the study variables, were used to obtain 120 participants in the study. The researcher administered questionnaires and interview guides to get the information. Results: Out of 120 participants, findings revealed that 75.5% (mean response of 2.0 with a standard deviation of 0.5) of the respondents agreed that training of staff motivates employees to produce quality work and services at Kikuube District Local government.   Conclusion: There is a significant relationship between employee training and the performance of the Kikuube district local government. Recommendation: Kikuube district local government should pass a resolution for continuous training of employees about evolving demands in the work field for further motivation, innovativeness, and creativity to stimulate the performance of employees leading to improved local government performance.